Development of Integrated Learning Supplements on Islamic Values for Reproductive System Materials to Enhance Critical Thinking Skills and the Religious Character of MA Students - Yuliati Khasanah; Lisdiana Lisdiana; Sigit Saptono; Ellianawati Ellianawati (Universitas Negeri Semarang, 2025)
In today's global era, education not only emphasizes cognitive aspects and critical thinking skills but also character formation and the internalization of moral values. One of the main challenges for Madrasah Aliyah is to integrate Islamic values into science learning so that students excel intellectually and have a strong religious character. This research aims to develop a valid and effective learning supplement that integrates Islamic values for use in reproductive system materials to strengthen students' critical thinking abilities and religious character. This research uses the ADDIE development model (Analyze, Design, Development, Implementation, and Evaluation), with data collected through interviews, observations, questionnaires, and tests (pre-post). The supplement was analyzed by experts in content and media and was tested on students from class XI IPA1 and XI IPA2 at MAN 2 Semarang and MAN Salatiga. Data analysis techniques used descriptive analysis and statistical data analysis. This supplement is declared very valid by media experts (93.37%) and material experts (95.49%), with a high readability level (88.18%). Strengthening critical thinking skills is shown through the N-Gain analysis per indicator with an average score of 0.82 (high category) and the religious character of students is indicated through the N-Gain analysis per indicator with an average score of 0.82 (high category).